The Block of Shaker K(+) Channels by κ-Conotoxin Pviia Is State Dependent - Terlau, Heinrich (The Rockefeller University Press, 1999)
κ-conotoxin PVIIA is the first conotoxin known to interact with voltage-gated potassium channels by inhibiting Shaker-mediated currents. We studied the mechanism of inhibition and concluded that PVIIA blocks the ion pore with a 1:1 stoichiometry and that binding to open or closed channels is very different. Open-channel properties are revealed by relaxations of partial block during step depolarizations, whereas double-pulse protocols characterize the slower reequilibration of closed-channel binding. In 2.5 mM-[K(+)](o), the IC(50) rises from a tonic value of ∼50 to ∼200 nM during openings at 0 mV, and it increases e-fold for about every 40-mV increase in voltage. The change involves mainly the voltage dependence and a 20-fold increase at 0 mV of the rate of PVIIA dissociation, but also a fivefold increase of the association rate. PVIIA binding to Shaker Δ6-46 channels lacking N-type inactivation or to wild phenotypes appears similar, but inactivation partially protects the latter from open-channel unblock. Raising [K(+)](o) to 115 mM has little effect on open-channel binding, but increases almost 10-fold the tonic IC(50) of PVIIA due to a decrease by the same factor of the toxin rate of association to closed channels. In analogy with charybdotoxin block, we attribute the acceleration of PVIIA dissociation from open channels to the voltage-dependent occupancy by K(+) ions of a site at the outer end of the conducting pore. We also argue that the occupancy of this site by external cations antagonizes on binding to closed channels, whereas the apparent competition disappears in open channels if the competing cation can move along the pore. It is concluded that PVIIA can also be a valuable tool for probing the state of ion permeation inside the pore.